2021
DOI: 10.1186/s12903-021-01602-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the use of virtual reality or dental smartphone applications as interventions for management of paediatric dental anxiety

Abstract: Background Virtual reality (VR) has been used successfully in medicine both as a distraction tool during procedures, and as an acclimatisation tool to prepare for a procedure or experience. It has not yet become widely used in dentistry, but could theoretically have a role in exposure-based acclimatisation for dental experiences. Methods To examine the use of VR or bespoke dental smartphone applications pre- or perioperatively in dentistry, to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…Moreover, VR applications are already applied, for example, on smartphones as distraction methods and acclimatization options for anxiety reduction during examinations and procedures for children and adults [26][27][28] or anatomy teaching. 23 In addition, a fully comprehensive VR dental learning environment of dental morphology teaching has already been presented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, VR applications are already applied, for example, on smartphones as distraction methods and acclimatization options for anxiety reduction during examinations and procedures for children and adults [26][27][28] or anatomy teaching. 23 In addition, a fully comprehensive VR dental learning environment of dental morphology teaching has already been presented.…”
Section: Introductionmentioning
confidence: 99%
“…29 The computer simulations are shown to be effective in teaching, with virtual teaching showing inconclusive results but very promising approaches. 2,23,26 Nevertheless, students or trainees reported higher confidence in realworld applications as a result of the applications. 6 In a review of 21 publications included, 74.0% of these showed improved learning using digital teaching (also partly VR) in medical education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On reviewing these existing dental applications (42)(43)(44)(45)(46)(47)(48), it was found that most of them monitor the patient's lifestyle and oral health status. None of them played a complete role in the whole process of patient treatment like WADA, including pre-treatment assessment, during-treatment advice, and posttreatment feedback.…”
Section: Discussionmentioning
confidence: 99%
“…VR had been used to augment the teaching of paediatric dentistry in the form of pre-clinical simulators for procedures such as paediatric dental restorations, pulpotomies and stainless steel crowns, with recent studies suggesting that VR simulations improved satisfaction and can be used as an adjunct in training dental students. 15,16 Although there had been some literature on harnessing the power of VR to prepare paediatric dental patients for procedures, 17 there is a paucity of research available on the effectiveness of virtual reality on teaching behaviour guidance in dental students.…”
mentioning
confidence: 99%